Effectiveness of Oral Fluid in Pathogenic Surveillance of Acute Respiratory Infection - Huang Qi; Sun Jingyi; Dong Mei; Wang Jinxiang; Huang Yanfei; Yu Xiali; Dong Jianping; Liu Fangyao; Zou Lin; Xie Hui; Huang Fang (Zoonoses)
Oral fluid (OF) is a new safe, non-invasive, convenient, and efficient biological sample that can be used for virus nucleic acid and antibody detection. Because few studies have performed surveillance of multiple respiratory pathogens, this study sought to explore the application value of OF in this field. OF and throat swabs were collected from December 2020 to December 2021 in patients with acute respiratory tract infections in Beijing. Multiplex real-time PCR was performed, and the detection performance of two samples was compared. A total of 769 OF and throat swab samples were collected. The detection rates of respiratory pathogens in throat swabs and OF were 29.26% (225/769) and 20.81% (160/769), respectively. The sensitivity and specificity of the OF assay, compared with the throat swab assay, were 71.11% (160/225) and 100% (544/544), respectively. The two assays had excellent agreement (kappa = 0.78). The detection consistency varied among pathogens. For OF samples, the most common pathogen was the influenza B virus, and the highest detection rate was in the ≤5-year-old group. The highest positivity rate was observed in December 2021. OF samples have excellent potential for the epidemiological surveillance of respiratory pathogens, and may have application prospects in preventing and controlling infectious diseases.